Robust secret image sharing resilient to global noise and region cropping attacks - Li, Peng; Tian, Hao; Yang, Ching-Nung (Digital signal processing, 2026)
In traditional (k, n)-threshold secret image sharing (SIS) schemes, the secret image can theoretically be reconstructed using k or more shadow images. However, in real-world environments, factors such as signal interference during transmission and degradation of storage media often cause shadow images to be compromised, which presents challenges for the practical application of traditional SIS schemes. To address this issue, we propose a robust secret image sharing scheme that is resilient to both global noise and region cropping attacks. The secret image undergoes a two-stage compression process involving Absolute Moment Block Truncation Coding (AMBTC) and quantization, generating shadow images that integrate dual compressed data components to enhance resistance to region cropping attacks. Additionally, we integrate Reed-Solomon codes and integer programming in the sharing phase to mitigate global noise effects, including Gaussian noise. The proposed scheme is effective in resisting both global noise and region cropping attacks, as well as their combination, while preserving the visual fidelity of reconstructed images. Experimental results demonstrate the robustness and efficacy under diverse attack scenarios.